Effect of Trace Elements on Biosorption of HG2+ By HG2+Tolerant Saccharomyces Cerevisiae A100 - KHUSHI MUKHERJEE; AJIT KUMAR BANIK (International Journal of Pharma and Bio Sciences, 2010)
Use of microorganisms for removing mercury (Hg++) is an effective technology for the treatment of industrial wastewaters and can become an effective tool for the remediation of man-impacted coastal ecosystems with this metal. In our laboratory a high Hg++ resistant Saccharomyces cerevisiaeA100 is already developed to facilitate Hg++ biosorption even from Hg++ rich solution. Inorganic anions and cations are essential for the growth and metabolism of Saccharomyces cerevisiaeA100 and also play significant role on biosorption process. Experiments revealed 0.15% K2HPO4, 0.06% KCl , 0.06% MgSO4,7H2O as the optimized inorganic ingredients of the nutrient medium (Glucose 5.0%, Urea 0.25%). Supplementation of nutrient broth with 1µg/ml FeSO4,7H2O, 5µg/ml MnSO4,H2O and 10µg/ml Na2MoO4,2H2O exhibit marked positive effect on biosorption of Hg++. Optimization of the concentration of inorganic nutrients enhances biosorption efficiency of Saccharomyces cerevisiaeA100 from 90% to 96.6% (developed significance level p<0.001) . Addition of CuSO4,5H2O; ZnSO4,7H2O; CoCl2,6H2O; NiSO4,7H2O; NH4VO3 to the biosorption medium was found to play inhibitory role on the growth and biosorption of Hg++ by Saccharomyces cerevisiaeA100.